2008
DOI: 10.1038/sj.ki.5002621
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of epidermal growth factor to monocyte chemotactic peptide-1 in the urine predicts renal prognosis in IgA nephropathy

Abstract: The production of cytokines by resident and non-resident renal cells during immunoglobulin A nephropathy (IgAN) plays a key role in the progression of renal damage. The aim of this study was to determine if measurements of urinary epidermal growth factor (EGF) and monocyte chemotactic peptide-1 (MCP-1), at the time of renal biopsy, were a predictor of end-stage renal disease (ESRD) in a cohort of 132 patients with biopsy-proven IgAN. Outcome measures were a doubling of the baseline serum creatinine (sCr) and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 19 publications
7
85
0
Order By: Relevance
“…Our second major finding was that ruboxistaurin was associated with reductions in GFR and filtration fraction without affecting ERPF in hyperfiltration subjects but was not associated with such reductions in normofiltration subjects. Furthermore, the change in the urinary biomarkers in hyperfiltration subjects was consistent with protection against renal injury (a decline in MCP-1 and a rise in the EGF-to-MCP-1 ratio) (12). Although we cannot determine the precise pathway responsible for these hemodynamic and molecular effects, we favor the theory that ruboxistaurin may have inhibited the effects of angiotensin II, leading to vasodilatation and a fall in GFR.…”
mentioning
confidence: 89%
“…Our second major finding was that ruboxistaurin was associated with reductions in GFR and filtration fraction without affecting ERPF in hyperfiltration subjects but was not associated with such reductions in normofiltration subjects. Furthermore, the change in the urinary biomarkers in hyperfiltration subjects was consistent with protection against renal injury (a decline in MCP-1 and a rise in the EGF-to-MCP-1 ratio) (12). Although we cannot determine the precise pathway responsible for these hemodynamic and molecular effects, we favor the theory that ruboxistaurin may have inhibited the effects of angiotensin II, leading to vasodilatation and a fall in GFR.…”
mentioning
confidence: 89%
“…On the other hand, epidermal growth factor (EGF), a peptide growth factor produced by the ascending loop of Henle and the distal convoluted tubule, seem to have a protective role in tubulointerstitial damage. Decreased renal EGF expression has been found in chronic kidney disease [13], and decreased urine EGF levels have been found in IgA nephropathy (IgAN) patients with advanced histopathological lesions [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, we previously found that urinary EGF excretion was a strong predictor of disease outcome in IgAN (7,48). Finally, in an animal model of brain ischemia, LG3 was shown to be neuroprotective and antiproliferative in brain endothelial cells (49).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, a few noninvasive diagnostic tests for detecting IgAN and a series of prognostic biomarkers have been suggested (4)(5)(6)(7)(8)(9)(10)(11)(12). However, the ability to accurately predict individual patient-level risk at the time of diagnosis or during early followup remains limited and mainly relies on clinical and histologic features (13).…”
Section: Introductionmentioning
confidence: 99%